Introduction to Cheminformatics. Issue 1 (24th March 2016) - Wishart, David S.
Abstract: Cheminformatics is a field of information technology that focuses on the collection, storage, analysis, and manipulation of chemical data. The chemical data of interest typically includes information on small molecule formulas, structures, properties, spectra, and activities (biological or industrial). Cheminformatics originally emerged as a vehicle to help the drug discovery and development process, however cheminformatics now plays an increasingly important role in many areas of biology, chemistry, and biochemistry. The intent of this unit is to give readers some introduction into the field of cheminformatics and to show how cheminformatics not only shares many similarities with the field of bioinformatics, but also enhances much of what is currently done in bioinformatics, molecular biology, and biochemistry. © 2016 by John Wiley & Sons, Inc.